STUDY OF THE CONSTRUCTION OF NON-RIGID ROAD PAVEMENT IN MOUNTAIN AREAS OF THE DAGESTAN REPUBLIC - T. G. Gasanov; E. Z. Batmanov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
Currently, an important national goal is to increase road construction with simultaneous improving of the quality, reliability and durability and reducing consumption of scarce materials. In this regard, at the forefront are the problems of scientifically grounded complex calculation methods of building structures for strength and durability, allowing on the basis of a full consideration of the actual condition of the material to make the optimal design of the road pavement.